Frank Davey and the Firing Squad - van Herk, Aritha (Studies in Canadian Literature, 2007)
Frank Davey's analyses of popular culture, nationalism, the media, and both print and material culture call to attention some of the hypocrisies practised behind the canonical drapes of Canadian literature. His early wrestlings with the discontents and self-deceptions of our critical practice taught critics and readers to be suspicious of paraphrase. But despite his sounding other alarms, his later discussions of our culture's continuing love affair with paraphrasis have been ignored. The critical silence that met his public and political texts Reading Kim Right (1993), Karla’s Web (1994) and Mr. and Mrs. G.G. (2003) is an indictment of our national collusion with a limited and limiting annotative or glossographic readerly practice. These “media” texts merit consideration as careful as that given Davey’s other poetical interventions.